Pengaruh Whistleblowing Triangle terhadap Intensi dalam Melakukan Whistleblowing - Ilham Maulana Saud; Putri Febriana (Universitas Swadaya Gunung Jati, 2022)
AbstractThe urgency to implement whistleblowing to identify and reveal the fraud is acknowledged by regulators all over the world. This research aims to determine of whistleblowing effect triangle, moral, or social incentives toward intention to do whistleblowing. By understanding the factors that generate the action of whistleblowing of fraud, we can come to the light of how it works. This study utilizes the quantity approach by using smartPLS version 3 as a data analysis tool. The technique of data collection is a questionnaire using a purposive sampling method by collecting samples of financial and accounting workers in companies in Indonesia that consist of 150 respondents in total. The results of the research showed that pressure, financial incentives, opportunities, rationalization, moral and social incentives positively and significantly affect the intention to do whistleblowing on financial and accounting staff who work in companies in Indonesia. The push factors that consist of financial incentives, opportunities, rationalization, moral and social incentives on this study when received by a person in disclosing fraud can affect the intensity of whistleblowing activities, so the higher push factors they have will be directly proportional to the person’s intentions in uncovering fraud.Keywords: Whistleblowing triangle; Moral or social incentives; Intention in whistleblowing; Fraud disclosing Abstrak Urgensi penerapan whistleblowing untuk mengindentifikasi dan mengungkap fraud diakui oleh regulator di seluruh dunia. Penelitian ini bertujuan untuk mengetahui efek whistleblowing triangle, insentif moral dan sosial terhadap niat untuk melakukan whistleblowing. Dengan memahami faktor-faktor yang menghasilkan tindakan whistleblowing atas kecurangan, kita dapat mengetahui cara kerjanya. Penelitian ini menggunakan smartPLS versi 3 sebagai alat analisis data. Teknik pengumpulan data yang diterapkan adalah kuesioner dan menerapkan metode purposive sampling dengan mengumpulkan data staf keuangan maupun akuntansi yang berasal dari perusahaan-perusahaan di Indonesia yang berjumlah 150 responden. Hasil penelitian ini menunjukkan bahwa tekanan, insentif keuangan, peluang, rasionalisasi, insentif moral dan sosial berpengaruh signifikan terhadap niat melaksanakan whistleblowing pada staf keuangan dan akuntansi yang bekerja di perusahaan-perusahaan di Indonesia. Faktor pendorong terdiri dari tekanan, insentif keuangan, peluang, rasionalisasi, insentif moral dan sosial pada penelitian ini ketika diterima oleh seseorang dalam pengungkapan kecurangan dapat mempengaruhi intensitas kegiatan whistleblowing, sehingga semakin tinggi faktor pendorong yang dimiliki akan berbanding lurus dengan niat orang tersebut dalam mengungkap kecurangan.Katakunci: Whistleblowing triangle; Insentif moral dan sosial, Intensi dalam melaksanakan whistleblowing; Pengungkapan kecurangan